Anggaran Pendidikan Era Otonomi Daerah Dalam Perspektif Constitutional Mandatory Spending: Studi Kebijakan Kartu Jakarta Pintar - Fikri, Abdullah; Sulfany, Abdiilah (Universitas Sang Bumi Ruwa Jurai, 2024)
Indonesia explicitly emphasizes the state's obligation to prioritize the education budget of at least 20% of the State Revenue and Expenditure Budget as well as the Regional Revenue and Expenditure Budget. The regional government's commitment to implementing its constitutional obligations still needs to be encouraged so that the education budget in the Regional Revenue and Expenditure Budget reaches 20% purely for education. The aim of this research is to determine the Jakarta Smart Card policy launched by the Special Capital Region of Jakarta government from the perspective of constitutional mandatory spending. This paper is normative legal research using primary legal materials in the form of laws and regulations relating to education and education budgets in DKI Jakarta. The results of this research show that the Jakarta Smart Card policy experiences constitutional fluctuations and inconsistencies regarding constitutional mandatory spending